Sexually transmitted disease prevalence in brothel-based commercial sex workers in Chiang Mai, Thailand: impact of the condom use campaign - Rugpao S. (2014)
One hundred and ninety five (195) brothel-based commercial sex workers (CSW) in Chiang Mai, Thailand, were screened for sexually transmitted disease (STD) between October 1994 and April 1995, prior to their enrollment in a multi-center comparative trial of the effectiveness of two strategies using male and female condoms. These CSW had a mean age of 22.2 (SD 4.3) years. Forty-seven per cent were Thai and 57.4 per cent had no formal education. Median duration of prostitution was 16 months and median cost for sexual service was 50 baht (US$ 2) per client. Ninety-four per cent of CSW reported always using condoms with clients. There were 63 (32.3%) CSW infected with at least one type of the STD screened. The prevalence of STD included chlamydial infection (16.9%), gonococcal infection (14.4%), condyloma accuminata (4.6%), moluscum contagiosum (2.6%) and trichomoniasis (1.0%). There was no statistically significant risk factor for STD found in this study. Despite an active programme for prevention of STD in CSW and the provision of free condoms, STD were diagnosed in one-third of the screened CSW in Chiang Mai. The programme needs to be strengthened by more intensive education and practice in the correct and consistent use of condoms and integrated with other STD prevention programmes.